Juridical Analysis of the Death Penalty for Perpetrators of Corruption as the Ultimate Remidium for Corruption Eradication in Indonesia - Mery Rohana Lisbeth Sibarani (Arbain Publishing, 2025)
The death penalty for perpetrators of corruption crimes is regulated in Article 2 of Law Number 31 of 1999 concerning the Eradication of Corruption Crimes jo. Law Number 20 of 2001 concerning Amendments to Law Number 31 of 1999 concerning the Eradication of Corruption Crimes (hereinafter referred to as the PTPK Law). The death penalty is imposed on perpetrators of corruption crimes with crimes that harm state finances under certain circumstances, namely perpetrators of corruption crimes commit corruption when the state is in danger in accordance with applicable laws, when a national natural disaster occurs, as a repetition of corruption crimes, or when the country is in a state of economic and monetary crisis. However, in Indonesia, the death penalty for convicted corruptors is still minimal, even corruption of the Minister of Social Affairs of the Republic of Indonesia, Juliari Batubara, was not sentenced to death and received leniency by a judge in a different trial than in China, even though the death penalty or uitvoering provides a deterrent effect for corrupt perpetrators that correlates with the eradication of corruption. This type of research is normative research. The result of this study is that the regulation of the death penalty in Indonesia is already contained in the Criminal Code and the special criminal law of the death penalty is also found in the Drug Law, the Terrorism Law, the Human Rights Court Law and PTPK. Both in general and special criminal law, the death penalty is only given to extra ordinary or very cruel crimes that have an impact on a wide audience. Indonesia has similarities in the application of the death penalty with China, namely providing the death penalty for corruption crimes and has carried out more executions of corruption convicts than Indonesia. Both countries prioritize human rights, so that the imposition of the death penalty has a waiting period and changes to life imprisonment if the convict shows efforts to improve commendable behavior and actions as well as the right to apply for clemency. The death penalty as the ultimate remidium in Indonesia has not been effective so that it cannot produce a deterrent effect for the eradication of corruption in Indonesia.